A clinicopathological study of leprosy: a study of skin biopsies - Tilva, Khushbu K.; Jethwani, Deepa; Dhruva, Gauravi (International Journal of Research in Medical Sciences, 2022)
Background: Leprosy is a chronic infectious granulomatous disease caused by Mycobacterium leprae. The disease mainly affects peripheral nervous system, the skin and other tissues such as the muscles, bones and joints, eyes, reticuloendothelial system, testis etc. To reduce global load of leprosy, it is essential to have an early and proper diagnosis by clinical and histopathological correlation followed by proper and complete treatment. Aims and Objectives were 1) to study histopathological spectrum of various subtypes of leprosy, 2) to study the age and gender wise incidence of different subtypes of leprosy, and 3) to assess the concordance between clinical and histological diagnosis in cases of leprosy using Ridley-Jopling scale. Methods: A retrospective observational study of 126 skin biopsies diagnosed as leprosy over a period of one year from August 2020 to July 2021 at P. D.U. Medical College and Hospital, Rajkot, Gujarat. Results: In this study, most of cases occurred in age group (21-40) years (50.8%) and showed marked male predominance with M:F ratio=2.7:1. Lepromatous leprosy (40.5%) was the most common histopathological type of leprosy. Maximum clinicopathological correlation seen in HL (100%), LL (90%) and TT (71.4%). Conclusions: Histopathological examination of skin biopsies and clinicopathological correlation both are essential for early and accurate diagnosis and typing of leprosy which is helpful in prevention of deformities and drug resistance by early and appropriate treatment.